Audit of turn-around times in a microbiology laboratory. Issue 3 (March 1991) - Rogers, S; Bywater, M J; Reeves, D S
Abstract : To determine the turn-around time in a microbiology laboratory a survey form was designed to collect data on the origin and type of specimen and the dates and times when (i) the sample was taken; (ii) the specimen was received in the laboratory; (iii) the report was signed by the microbiologist; (iv) the report was sorted by the laboratory clerical staff; and (v) the final report was received on the ward. The cumulative time from sampling to a result arriving on the ward was 51.5 (SD 28.6) hours. The survey is a simple method of determining turn-around time and high-lighted minor deficiencies in the service which were easily rectified.